НАУЧНО-ТЕХНИЧЕСКИЙ И МЕТОДИЧЕСКИЙ ПОИСК НОВЫХ СПОСОБОВ И СРЕДСТВ В ДОСТИЖЕНИИ ОБРАЗОВАТЕЛЬНЫХ ЦЕЛЕЙ ПРИ ИЗУЧЕНИИ ИНОСТРАННЫХ ЯЗЫКОВ - Абдуллаева, Р.А.; Джуманиязова, Н.А. (SCIENCE and SOCIETY, 2025)
The article talks about the effectiveness of using innovative technologies for the development of a teacher’s creative abilities, which today is very important to move from reproductive teaching methods to productive ones, when students must not only show an understanding of the phenomenon being studied, but also solve problems, revealing the cause-and-effect relationships between them, be able to connect the material being studied with practice, with life.
Keywords: pedagogy; development; technology; Internet; realization; computer